Dimensionality-dependent oxygen reduction activity on doped graphene: Is graphene a promising substrate for electrocatalysis?. (January 2015) - Chung, Min Wook; Choi, Chang Hyuck; Lee, Seung Yong; Woo, Seong Ihl
Abstract: Graphene, a two-dimensional layer framework of sp 2 -hybridized carbon, has attracted tremendous attentions as a promising material for oxygen reduction reactions (ORRs) due to its ideal uniqueness of high surface area and electrical conductivity. Contrary to the general belief, however, graphene catalysts have shown poor catalytic activities compared with those of other carbon-based catalysts. Herein, to understand the low ORR kinetics on the graphene catalysts, the dimensionality of graphene catalysts is sequentially tuned from sheets (2D) to ribbons (1D) and to dots (0D), and then the accompanying changes in terms of physical and electrochemical properties are investigated. In ultraviolet photoelectron spectroscopy, an increment in electropotential is measured as the dimensionality of the graphene catalysts decreases, of which the result infers the enhanced kinetics of the electron transfer from the graphene catalysts to O2 (electropotential: 0D>1D>2D). However, ORR performance does not follow the order of electropotential, and the graphene ribbons show the best activity among the prepared graphene catalysts (ORR activity: 1D>0D>2D). Further electrochemical impedance spectroscopy studies demonstrate that ORR kinetics is primarily determined by charge transfer rates in the fabricated graphene electrodes, which are strongly related to the electrode configurations and thus also to the length-to-width ratios of the graphene catalysts. The graphene sheets and dots, of which the length-to-width ratios are almost 1, handily lay over each other, leading to an impedance of efficient charge transfers. This study suggests the importance of void channels in the fabricated graphene electrode, which have not previously been considered significantly as a factor for improving ORR activity on the graphene catalysts. Graphical abstract: Highlights: The dimensionality of graphene catalysts is sequentially tuned from sheets (2D) to ribbons (1D) and to dots (0D), and then the accompanying changes in terms of physical and electrochemical properties are investigated. The prepared graphene catalysts, having N-doped sites as active sites, revealed an increment of electropotential as the dimensionality decreased, but the catalytic activity did not perfectly follow the tendency. Electrochemical impedance spectroscopy studies demonstrate that ORR kinetics is primarily determined by charge transfer rates in the fabricated graphene electrodes. To achieve a superior ORR performance, the structural constitute for efficient charge accessibility as well increased E P may be preferentially considered in future design of graphene catalysts.